The Search for and Presence of Calling: Latent Profiles and Relationships With Work Meaning and Job Satisfaction - Li, Feifei (Front Psychol, 2021)
Previous studies showed inconsistent results on the association between searching for calling and its psychosocial functioning outcomes (i.e., work meaning and job satisfaction). The link of searching for calling to its psychosocial functioning outcomes may be influenced by the presence of calling because the search for and presence of calling can co-exist within individuals. Thus, the present study employed a person-centered method (latent profile analysis) to identify subgroups combining the search for and presence of a calling and then explore the identified profiles' differences in work meaning and job satisfaction. Study participants were Chinese kindergarten teachers (n = 726). Latent profile analysis revealed four different groups: (1) actively maintaining calling (24.93%), (2) unsustainable calling (11.43%), (3) moderately increasing calling (23.14%), and (4) actively increasing calling (40.50%). Subsequent analyses showed notable differences across the four groups on work meaning and job satisfaction. Participants in profile 1 with both the highest searching for and presence of calling would experience more work meaning and job satisfaction than those in the other profiles whose strengths of searching for and presence of calling were relatively low. Participants in profile 4 had higher searching for and presence of calling than those in profile 3, and they experienced more meaningfulness at work and were more satisfied with their job. These findings indicate that actively searching for calling is closely associated with more work meaning and job satisfaction among people who already perceive intensive calling. Implications, limitations, and future directions of the results are discussed.